A Major QTL for Resistance to Vibrio anguillarum in Rainbow Trout - Karami, Asma M.; Ødegård, Jørgen; Marana, Moonika H.; Zuo, Shaozhi; Jaafar, Rzgar; Mathiessen, Heidi; von Gersdorff Jørgensen, Louise; Kania, Per W.; Dalsgaard, Inger; Nielsen, Torben; Buchmann, Kurt (Frontiers in Genetics, 2020)
Genetic selection of disease resistant fish is a major strategy to improve health, welfare and sustainability in aquaculture. Mapping of single nucleotide polymorphisms (SNP) in the fish genome may be a fruitful tool to define relevant quantitative trait loci (QTL) and we here show its use for characterization of Vibrio anguillarum resistant rainbow trout (Oncorhynchus mykiss). Fingerlings were exposed to the pathogen V. anguillarum serotype O1 in a solution of 1.5x107 cfu/ml and observed for 14 d. Disease signs appeared three days post exposure (dpe) whereafter mortality progressed exponentially until 6 dpe reaching a total mortality of 55% within 11 days. DNA was sampled from all fish - including survivors - and analyzed on a 57k Affymetrix SNP platform whereby it was shown that disease resistance was associated with a major QTL on chromosome 21 (Omy 21). Gene expression analyses showed that diseased fish activated genes associated with innate and adaptive immune responses. The possible genes associated with resistance are discussed.